Description of the final stadium larvae of Onychargia atrocyana Selys, 1865 from Sarawak, identified using DNA barcoding (Odonata: Zygoptera: Platycnemididae), with an overview of larval characters in the Platycnemididae - Orr, Albert G.; Dow, Rory A. (Zootaxa, 2015)
The final stadium larva of Onychargia atrocyana Selys, 1865, is described and illustrated based on two female specimens collected at Gunung Mulu National Park, Sarawak, East Malaysia. The larvae were identified by matching the mitochondrial marker COI with that of known adult specimens from Gunung Mulu, Bintulu and Kuching in Sarawak and from Pahang state in West Malaysia. The specimens presented close matches with all adults in this gene. As O. atrocyana is a taxonomically isolated species with no close congeners in Borneo the determination is beyond doubt. O. atrocyana is the only member of the Onychargiinae for which the larva is known. It is compared with the known larvae of other platycnemidid subfamilies, and the possible significance of larval morphology in higher classification of the group is discussed.